Golden Goal - Freedman, Dan (London Scholastic, 2009)
There's a massive buzz around Jamie Johnson. His dreams of becoming a professional footballer seem to be coming true, after years of hoping and practising. But, just when he seems close to living the dream, a shocking event turns his world upside down. Jamie finds himself facing his toughest times yet. He's never been a quitter, but can he rise to the challenge
Keywords: Ambition -- Soccer players -- Johnson, Jamie (Fictitious character) -- Juvenile fiction